The Quality Test of Bokasi Fertilizer a Combination of Local Ingredients from the Leaves of Gamal, Kirinyuh and Lamtoro Plant Leaves - Yermias Windi; Uska Peku Jawang; Melycorianda H. Ndapamuri (Asian Journal of Healthcare Analytics, 2022)
The purpose of the study was to determine the quality of Bokasi fertilizer with a combination of local ingredients, namely gamal leaves, kirinyuh leaves, and lamtoro leaves. The method used is purposive sampling on the combination of local materials (P1 = 5 Gamal + 2.5 Kirinyuh + 2.5 Lamtoro; P2 = 2.5 Gamal + 5 Kirinyuh + 2.5 Lamtoro; P3 = 2.5 Gamal + 2.5 Kirinyuh +5Lamtoro; P4= 4Gamal +3Kirinyuh +3 Lamtoro; P5=3Gamal +4Kirinyuh + 3Lamtoro; and P6= 3Gamal +3Kirinyuh +4Lamtoro). Determination of the quality of bokasi fertilizer based on SNI 19-7003-2004. Parameters tested were pH, electrical conductivity (DHL), C-Organic, N-Total, C/N Ratio, Phosphorus, and Potassium. The test results obtained the value of pH (6.79-6.88), C-Organic (16.04-22.48), N-Total (2.96-3.30), C/N Ratio (5.22- 7.14), Phosphorus (0.63-0.64), Potassium (1.24-1.59), and DHL (3.59-4.26). Based on SNI 19-7003-2004 obtained pH, C-Organic, N, P, K meet the standard, while the C/N ratio does not meet the standard. High DHL indicates the value of fertilizer nutrients available to plants.